Historical atmospheric pollution trends in Southeast Asia inferred from lake sediment records - Engels, S.; Fong, L.S.R.Z.; Chen, Q.; Leng, Melanie J.; McGowan, Suzanne; Idris, M.; Rose, N.L.; Ruslan, M.S.; Taylor, D.; Yang, H. (Elsevier, 2018)
Fossil fuel combustion leads to increased levels of air pollution, which negatively affects human health as well as the environment. Documented data for Southeast Asia (SEA) show a strong increase in fossil fuel consumption since 1980, but information on coal and oil combustion before 1980 is not widely available. Spheroidal carbonaceous particles (SCPs) and heavy metals, such as mercury (Hg), are emitted as by-products of fossil fuel combustion and may accumulate in sediments following atmospheric fallout. Here we use sediment SCP and Hg records from several freshwater lentic ecosystems in SEA (Malaysia, Philippines, Singapore) to reconstruct long-term, region-wide variations in levels of these two key atmospheric pollution indicators. The age-depth models of Philippine sediment cores do not reach back far enough to date first SCP presence, but single SCP occurrences are first observed between 1925 and 1950 for a Malaysian site. Increasing SCP flux is observed at our sites from 1960 onward, although individual sites show minor differences in trends. SCP fluxes show a general decline after 2000 at each of our study sites. While the records show broadly similar temporal trends across SEA, absolute SCP fluxes differ between sites, with a record from Malaysia showing SCP fluxes that are two orders of magnitude lower than records from the Philippines. Similar trends in records from China and Japan represent the emergence of atmospheric pollution as a broadly-based inter-region environmental problem during the 20th century. Hg fluxes were relatively stable from the second half of the 20th century onward. As catchment soils are also contaminated with atmospheric Hg, future soil erosion can be expected to lead to enhanced Hg flux into surface waters.